Answer:
x/6
Step-by-step explanation:
Use x to represent "a number" bc u dont know exactly what that number is.
Answer:
x = -5 y = -3
Step-by-step explanation:
-3x + 2y = 9
multiply the 2nd equation by 3 to set it up for elimination
3(x - 3y)= 3(4)
3x-9y = 12
so now combine both to add
-3x + 2y = 9
3x - 9y = 12
Adding both gives you
-7y = 21
divide both by -7 and you get
y = -3
and you substitute y back into equation to get x
x - 3 (-3) = 4 gives you
x + 9 = 4
x = 4 - 9
x = -5
Answer is provided in the image attached.
Answer:
See below
Step-by-step explanation:
Expand L side to get
4n -12 -2n < -10 + 2n simplify L side
2n -12 < -10 +2n subtract 2n from both sides
<u>-12 < -10 </u> <===== so the equation is true for ALL n
(-∞ , + ∞ )
Answer:
5) y=5
6)x=7
7)a=18
Step-by-step explanation:
5) y= any number will work. don't add a variable like x
6)x= any number will work. don't add a variable
My work for 7 is in the picture. If you'd like me to explain more for 7 lmk :)